Housing As We Grow Older: Community Support Services - Virginia Peart; Carolyn Wilken (EDIS, 2003)
This document is Fact Sheet FCS 3191, a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: November 2002. First published: January 1994. Revised: November 2002. Originally published as SAH-4. Adapted for use in Florida from "Housing as We Grow Older: Community Support Services," and "Tomorrow's Choices."